Conformations of A-DNA and B-DNA in agreement with fiber X-ray and infrared dichroism. - Premilat, S (1983)
Two right handed double helices are proposed as models for DNA fibers in respectively the A and the B form. The present conformations have geometrical parameters which agree very well with fiber X-ray and the orientation of their phosphate groups is in good accordance with infrared dichroïsm measurements. Dihedral angles and complete sets of atomic coordinates are given together with stereo-views and curves of the calculated diffracted intensities. Results are compared with experimental data and with preceding DNA models.